2016
DOI: 10.5424/sjar/2016143-9339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the spray volume adjustment model on the efficiency of fungicides and residues in processing tomato

Abstract: This study compared the effects of a proportionate spray volume (PSV) adjustment model and a fixed model (300 L/ha) on the infestation of processing tomato with potato late blight (Phytophthora infestans (Mont.) de Bary) (PLB) and azoxystrobin and chlorothalonil residues in fruits in three consecutive seasons. The fungicides were applied in alternating system with or without two spreader adjuvants. The proportionate spray volume adjustment model was based on the number of leaves on plants and spray volume inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…There is little research into the effects of the tested adjuvant in the literature and we only found two published papers. Ratajkiewicz et al (2016) reported that when that multi-functional adjuvant was used with a half dose of chlorothalonil and azoxystrobin against potato late blight caused by Phytophthora infestans (Mont.) in tomato, the adjuvant reduced residues in tomato under the fixed model spray volume.…”
Section: Discussionmentioning
confidence: 99%
“…There is little research into the effects of the tested adjuvant in the literature and we only found two published papers. Ratajkiewicz et al (2016) reported that when that multi-functional adjuvant was used with a half dose of chlorothalonil and azoxystrobin against potato late blight caused by Phytophthora infestans (Mont.) in tomato, the adjuvant reduced residues in tomato under the fixed model spray volume.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the infestation of the plants, a determination was made of the influence of the constant (300 L/ha, SV300) and variable (PSV) spray volume and adjuvants when alternating azoxystrobin and chlorothalonil for coarse spraying with the IDKT12003 twin-jet induction nozzle. The variable spray volume (PSV) was calculated from the number of leaves per plant according to the model presented in the paper [38]. In accordance with the methodology described in the article, two fungicides were used in the study alternatively: azoxystrobin (methyl (E)-2-[2-[6-(2-cyanophenoxy)pyrimidine-4-yl]oxyphenyl]-3-methoxyprop-2-enoate, Amistar 250 SC; Syngenta Ltd., Guildford, UK) at a dose of 125 g/ha (50% of the recommended dose) or chlorothalonil (2,4,5,6-tetrachlorobenzene-1,3-dicarbonitrile, Gwarant 500 SC; Arysta LifeScience S.A.S., Noguères, France) at a rate of 625 g/ha (50% of the recommended dose).…”
Section: Methodsmentioning
confidence: 99%